Autophagy in kidney disease and aging: lessons from rodent models - Lenoir, Olivia; Tharaux, Pierre-Louis; Huber, Tobias B (Kidney international, 2016)
Autophagy is a highly regulated lysosomal protein degradation pathway that removes protein aggregates and damaged or excess organelles to maintain intracellular homeostasis and cell integrity. Dysregulation of autophagy is involved in the pathogenesis of a variety of metabolic and age-related diseases. Growing evidence suggests that autophagy is implicated in cell injury during renal diseases, both in the tubulointerstitial compartment and in glomeruli. Nevertheless, the impact of autophagy on renal disease progression and aging is still not fully understood. This review summarizes the recent advances in understanding the role of autophagy for kidney disease and aging.